DIFFERENTIATING VULGAR PSORIASIS AND TINEA INCOGNITO: CHALLENGES AND IMPLICATIONS FOR HEALTHCARE PROFESSIONALS - Bonon, Milena Raquel Charbel Dias (Revista Sistemática, 2024)
Differentiating between vulgar psoriasis and tinea incognito presents a significant challenge for healthcare professionals due to their overlapping clinical manifestations. Both conditions exhibit erythematous and scaly lesions but differ fundamentally in etiology and treatment approaches. Psoriasis is a chronic autoimmune disorder requiring targeted therapies such as topical agents, phototherapy, and systemic medications. In contrast, tinea incognito, a fungal infection, necessitates appropriate antifungal treatments. Recent studies emphasize the critical need for accurate diagnosis, highlighting that a thorough clinical history, distinctive lesion characteristics, and laboratory tests—such as fungal cultures and skin biopsies—are essential to prevent misdiagnosis. The rising incidence of tinea incognito, often exacerbated by the inappropriate use of topical corticosteroids, illustrates the importance of recognizing its atypical manifestations and underscores the need for careful clinical assessment. Interdisciplinary collaboration among healthcare professionals, alongside continuous education, is vital for ensuring the proper identification and management of these dermatological conditions. This proactive approach can significantly reduce the risk of incorrect diagnoses and inappropriate treatments. Understanding the underlying mechanisms and clinical presentations of both vulgar psoriasis and tinea incognito is crucial for improving patient outcomes. It also highlights the importance of monitoring at-risk populations to promote more effective, evidence-based dermatological practices. Overall, a heightened awareness and comprehensive understanding of these conditions will facilitate better clinical decision-making, leading to improved patient care and enhanced management strategies for dermatological disorders.